Educational Process in Iraq: Course and Interference Options A social field study - Abd Jabr Al-Khafaji, Waleed (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to shed light on the path of the educational process in Iraq and the most important challenges it faces in order to set a future vision as options for advancing and upgrading the educational system in Iraq The study’s importance is reflected in the focus on the investment in education and knowledge building since it is regarded as the most powerful factor in the path of social transformation and human development As for the research methodology, several scientific methods have been employed to achieve the objectives of the research in order to capture the aspects of the phenomenon being studied . On the field side , the research relied on an intentional sample consisting of 50 experts (males and females) from the Ministry of Education and those with high certificates. They represent, at the same time, the size of the original community from which the sample was drawn . This community is a homogenous society in most of its characteristics . The researcher conducts an exploratory study of the sample before distributing the questionnaire, which consists of three axes that include 29 questions about the pillars of the educational process. To the consistency and high The Alpha-Cronbach coefficient test method was used to calculate the percentage of agreement (consistency) The average agreement (86) indicates a high consistency and correlation between the questionnaire paragraphs. The necessary results and proposal are identified as options for addressing the research problem at hand.